UNIVERSITY FINANCIAL AUTONOMY: EXPERIENCE OF LATVIA - Vlasova, Inna (Educological discourse, 2019)
The analysis of legislative support of higher education of Latvia was carried out. It was defined, that institutions of higher education are autonomous institutions of education and science with the right to self-government. The autonomy of higher education institutions is characterised by the division of power and responsibility between the State authorities and the management of the institution of higher education, as well as between the management and the academic staff. The sources of funding of higher education institutions from state sources were found out. They include the financial resources of the state budget for education; income from tuition fees; targeted financial resources. The types of economic activity of higher education institutions were determined. The components of the system of state funding of higher education institutions were highlighted: formula funding (basic funding of studies), which is related to the number of study places; performance agreements for preparation of a certain number of specialists and for development of scientific activity; 3) formula funding (basic funding of science) for institutions of higher education, scientific institutions, and scientific institutes established by institutions of higher education; 4) funding to scientific activities through competitions. The allocation methods of state financial resources for higher education institutions were determined. The first one includes direct allocations from the state budget to higher education institutions. The second one involves indirect subsidies through state-guaranteed loans. The components of new three-pillar model of state higher education funding were presented. They are: basic (base) funding, performance funding, and innovation- and profile-oriented financing. The analysis of financial autonomy indicators of universities was carried out.